Measurements of sustainability performance in hotels (+ case study - intercontinental Lisbon and the green key certification - Lacerda, Filipa Moutinho de Gouveia Correia de (2023)
This work project’s individual parts present an overview of sustainability certifications used by hotels from different brands worldwide, their motivations, and sustainability indicators as well as tools to measure these indicators. Moreover, best practices in hotel operations and their implementation are discussed. Lastly, the influence that green practices have on guests’ behavior when choosing a hotel is explored. The case study is based on this research and stresses the importance of sustainability certifications in the hotel industry. It explores the topic of such certifications for a five-star luxury hotel, the InterContinental Lisbon, identifies the most suitable certification for this hotel, and gives recommendations for its achievement.